SMART INHALER DALAM PENATALAKSANAAN ASMA: STUDI TERKINI TENTANG PENINGKATAN KEPATUHAN TERAPI DAN HASIL KLINIS - Salsabela (Universitas Pekalongan, 2025)
Background: Asthma is the most common chronic respiratory disease worldwide, with suboptimal adherence to maintenance therapy, resulting in increased exacerbations, hospitalizations, and mortality. Digital interventions, including electronic monitoring devices, smart inhalers, smart spacers, mobile applications, and SMS reminders, have emerged as innovative strategies to improve adherence and clinical outcomes. Objective: To evaluate the effectiveness of digital interventions in enhancing adherence to maintenance therapy in asthma patients, assess clinical and economic impacts. Method: Review was conducted on eight RCTs and observational studies evaluating digital interventions in adult and pediatric asthma patients. Key outcomes included adherence, inhaler technique, asthma control, quality of life, exacerbation prediction, and cost-effectiveness. Result: Digital interventions consistently improved adherence by up to 23% compared with control, enhanced inhalation technique, and improved asthma control and quality of life. Machine learning algorithms integrated with smart inhalers accurately predicted impending exacerbations, allowing proactive management. Long-term studies indicated cost savings through reduced use of add-on biologic therapies. In children, adherence and inhaler technique were shown to be distinct aspects, requiring targeted educational strategies. Conclusion: Digital interventions effectively improve adherence and clinical outcomes in asthma patients. These strategies have potential to support personalized and cost-effective asthma management. Further research is needed to evaluate long-term effectiveness and real-world implementation.